GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU PENGGUNAAN APD PADA KARYAWAN SAWIT DI PABRIK PT AGRONUSA INVESTAMA (PT ANI) DESA PAHAUMAN KEC. SENGAH TEMILA KAB. LANDAK 2022 - Karina Junita; Nurul Amaliyah; Suharno (Journal of Environmental Health and Sanitation Technology, 2023)
Personal protective equipment was a tool that could protect against accident hazards. The interview results this factory, there were work accidents such as being hit by palm fruit bunches, dust and one of the workers had an accident at work on a production machine. Still, here there was no recorded accident report. PT ANI was a palm oil processing company located in Pahauman Village, Sengah Temila district. ). This study aimed to describe the knowledge and behavior of using PPE in oil palm employees at the PT ANI factory, Pahauman Village, Sengah Temila District, Landak Regency. The population in this study found 78 people, and the sample of this study was all of them. The results showed that of the 78 workers who had good knowledge were 64 workers (82.06%), who have sufficient knowledge as many as 14 workers (17.94%), and who have a supportive attitude are 67 people (85.9%) and not supporting 11 workers (14.10%). Workers' behavior regarding the use of PPE 38 workers (48.72%), and 40 workers who have negative behavior (51.28). Overall the workers have good knowledge and are supportive in the use of PPE, but most of the workers show negative behavioral sentiments.